N-(2-Chloroethyl)pyrazine-2-carboxamide - da Silva Lima, C.H.; de Souza, M.V.N.; Wardell, S.M.S.V.; Wardell, J.L.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title molecule, C7H8ClN3O, the pyrazine and amide groups are almost co-planar [N-C-C-N torsion angle = -2.4 (2) degrees], a conformation stabilized by an intramolecular N-H center dot center dot center dot N hydrogen bond. The chloroethyl group lies out of the plane [N-C-C-Cl = -65.06 (17) degrees]. In the crystal, the presence of N-H center dot center dot center dot N hydrogen bonds leads to the formation of a C(6) supramolecular chain along the b axis. The carbonyl-O atom accepts two C-H center dot center dot center dot O interactions. These, plus Cl center dot center dot center dot Cl short contacts [3.3653 (6) angstrom], consolidate the packing of the chains in the crystal.